Study on the Anticollision Performance of a New Corrugated Steel Protection System for Bridge Pier - Guicheng Chen; Haidong Huang; Zhongfu Xiang (Shock and Vibration)
A new type of corrugated steel protection system (CSP) for the bridge pier is proposed to improve the impact resistance of the bridge pier and reduce the loss caused by the collision of the ship against the pier. A new bolt numerical simulation method and finite element model establishment method are proposed and verified by the impact test. The results show that the new method can effectively simulate the mechanical behavior of bolts and CSP. Parameters analysis was carried out subsequently by the verified finite element model which showed that the energy absorbing ability of CSP increases with corrugated steel pipe wall thickness and its weight decreases. It is concluded that CSP (2.0 mm) is the optimal structural type, and compared with the existing FRP Fender System. The results show that the energy absorbing ability of CSP (2.0 mm) is strong, and its final absorbed energy can reach 86.13% of the total energy of the model structural system (7.22 MJ).